1948
DOI: 10.6028/jres.041.043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of boron on the hardenability of high-purity alloys and commercial steels

Abstract: A st ud y was made of t he action of boron in relation to the hardenability of high-purity alloys varying in carbon content. The effectiveness of boron in enhancing the harden ability of t hese alloys and certain steels is believed to be due to its action in retarding the rate of nucleation of ferri te and carbide while in soli d solution in austenite. The hardenabi li ty of t he boron-treated a ll oys, as determined in terms of the cri tical coolin g rate of small specimens a usteniti zed at a ,vide range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

1953
1953
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 4 publications
0
8
0
3
Order By: Relevance
“…Deboronization is an important aspect to be considered in boron‐alloyed steels, as using high temperatures during heat treatments can result in partial or complete loss of boron in the surface region . Boron loss from the surface into depths of up to 0.5 mm at temperatures above 900 °C for 2 h has been attributed to oxidation effects .…”
Section: Influence Of Boron On Hardenabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…Deboronization is an important aspect to be considered in boron‐alloyed steels, as using high temperatures during heat treatments can result in partial or complete loss of boron in the surface region . Boron loss from the surface into depths of up to 0.5 mm at temperatures above 900 °C for 2 h has been attributed to oxidation effects .…”
Section: Influence Of Boron On Hardenabilitymentioning
confidence: 99%
“…Boron loss from the surface into depths of up to 0.5 mm at temperatures above 900 °C for 2 h has been attributed to oxidation effects . Moreover, Digges et al reported about a loss of boron in the decarburized zone of steels, which can be explained by the fact that the diffusion rate is comparable to that of carbon.…”
Section: Influence Of Boron On Hardenabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Aumento de 500 X. Ataque: Picral-4%. [29] . Figura 21 -Amostra de dimensões 12x12x55 mm de aço com baixo teor de carbono (AISI 4010), temperado e revenido (950°C-30min, têmpera em óleo + revenimentos 625°C-60min).…”
Section: Lista De Figurasunclassified